2014
DOI: 10.1097/sla.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Endoscopic Duodenal-Jejunal Bypass Liner on Obesity and Type 2 Diabetes Mellitus, a Multicenter Randomized Controlled Trial

Abstract: The DJBL is a safe and effective alternative to invasive bariatric procedures. Six months of DJBL treatment combined with diet leads to superior weight loss and improvement of T2DM when compared with diet alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 37 publications
(59 reference statements)
4
96
1
4
Order By: Relevance
“…Previous studies have shown that after extraction of DJBL, body weight partially increases and glucose control slightly deteriorates, but some of its effects still persist (de Jonge et al 2013b, Koehestanie et al 2014. Here, we show that 3 months after its removal, DJBL-associated body weight reduction was still present with an average regain of 3 kg from 12 kg that was lost.…”
Section: :1supporting
confidence: 59%
“…Previous studies have shown that after extraction of DJBL, body weight partially increases and glucose control slightly deteriorates, but some of its effects still persist (de Jonge et al 2013b, Koehestanie et al 2014. Here, we show that 3 months after its removal, DJBL-associated body weight reduction was still present with an average regain of 3 kg from 12 kg that was lost.…”
Section: :1supporting
confidence: 59%
“…Sixty-eight studies were used to calculate adverse events and early removal rates, 10 45,79 For the EndoBarrier DJBS meta-analyses, 11 studies met inclusion criteria. [92][93][94][95][96][97][98][99][100][101][102] Of these, 9 reported adverse events and early removal rates, 92-97,99-101 3 reported %EWL at 12 months, 97,100,101 4 were RCTs that reported %EWL over a sham or control group at device removal, 92,94,95,100 9 reported changes in glycosylated hemoglobin (HgA 1c ), 92,93,[95][96][97][98][99][100]102 and 3 reported changes in HgA 1c over a sham or control group in RCTs. 93,95,100 %EWL at 12 months and mean difference in %EWL over a control group for primary EBTs Orbera IGB.…”
Section: Search Resultsmentioning
confidence: 96%
“…The DJBL is comprised of a nitinol anchor, which is used to reversibly affix the device to the wall of the duodenal bulb [12][13][14][15]. Before reimplantation, all patients were examined with a gastroduodenoscopy to evaluate the state of the duodenal bulb, which was where the DJBL anchor was positioned.…”
Section: Anatomic Change In Duodenal Bulb Per-implantation and Postexmentioning
confidence: 99%
“…All rights reserved. bypass liner (DJBL, GI Dynamics, Lexington, MA, USA), which has shown promising results so far [14][15][16].…”
mentioning
confidence: 99%